Food need and fertilizer policy - Malavolta, E. (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the central role of fertilizers in the increase of agricultural production. The following points have been discussed in detail: 1. Goals of the primary sector of the economy; 2 Relationships between fertilizer requirements in Brazil; 3. Consumption, production and fertilizer requirements in Brazil; 4. Fertilizer policy in terms of research, extension, adaptation of technology of production, legislation and quality control, transport, credit and subsidies.